2017
DOI: 10.1109/tim.2017.2676218
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring Corrosion Process of Reinforced Concrete Structure Using FBG Strain Sensor

Abstract: Major factor effects the durability of a concrete structures is cracks formation induced by expansion of reinforcement corrosion. Therefore, monitoring and evaluating the corrosion level of structure is essential for its safety. In order to monitor corrosion, an innovative methodology based on Fiber Bragg Grating sensing technique was developed and tested in this paper. The method uses the volume of corrosion products to detect the evolution of corrosion. The corrosion process was accelerated by impressed curr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(24 citation statements)
references
References 25 publications
0
23
0
1
Order By: Relevance
“…SHM of concrete structure was discussed in Ref. 97, using polystyrene foam covered FBG. The expansion of corrosion induces formation of cracks in a concrete structure, which degrades the durability of concrete.…”
Section: Fbg-based Strain Sensorsmentioning
confidence: 99%
“…SHM of concrete structure was discussed in Ref. 97, using polystyrene foam covered FBG. The expansion of corrosion induces formation of cracks in a concrete structure, which degrades the durability of concrete.…”
Section: Fbg-based Strain Sensorsmentioning
confidence: 99%
“…With the reinforcement confined by concrete, this increase of volume introduces internal tensile stresses in the surrounding concrete, leading, when this tension exceeds the tensile strength of the concrete, to its cracking [45,46]. Almubaied et al studied the behavior of the FBG sensors installed on the face of the armature and concluded that the sensors have a good sensitivity to the progression of the corrosion process [47].…”
Section: Fiber Bragg Gratingmentioning
confidence: 99%
“…In addition, many researchers have developed sensors to detect atmospheric corrosion using radio-frequency identification (RFID) sensors [5][6][7], passive wireless sensors [8], corrosion potential sensors [9], optic sensors, fibre Bragg gratings (FBGs) [10][11][12][13][14][15], atmospheric corrosion monitoring (ACM) methods [16,17], and atmospheric corrosion rate monitoring (ACRM) techniques [18].…”
Section: Introductionmentioning
confidence: 99%